Law Enforcement in Indonesia for the Prevention of Human Organ Trafficking from a Pancasila Perspective - Franciscus Xaverius Wartoyo; Meivina Jayanti; Dewi; Lee Yong Hwa (Jurnal Smart Hukum (JSH), 2026)
From the perspectives of human rights and Pancasila, this article presents a comprehensive analysis of illegal human organ trafficking as one of the most serious crimes against humanity in the contemporary global context. The illegal trade in human organs continues to expand alongside the increasing medical demand for organ transplantation, which is not proportional to the availability of legally obtained organs, thereby encouraging the commodification of the human body and the exploitation of vulnerable groups. From a human rights perspective, illegal human organ trafficking constitutes a serious violation of the right to life, the right to bodily integrity, personal liberty, and the prohibition of torture and cruel, inhuman, or degrading treatment. In positive law, this practice is strictly regulated and sanctioned under Law No. 1 of 2023 on the New Criminal Code, particularly Article 345 in conjunction with Article 79 paragraph (1) letters d and f, which note that perpetrators of organ or human tissue trafficking may face imprisonment of up to seven years and a maximum category VI fine of IDR 2 billion. In addition, the Health Law Article 33 paragraph (2), strengthened by Government Regulation No. 28 of 2024, affirms the obligation to protect the human body and prohibits the illegal exploitation of human organs. This article argues that illegal human organ trafficking must not be understood merely as a medical or criminal issue, but rather as a profound moral, ethical, and ideological crisis that directly contradicts Pancasila as the philosophical foundation of the state. Therefore, this study emphasizes the importance of firm law enforcement grounded in the values of Pancasila and human rights to ensure that the human body is not commodified, but instead respected as an integral expression of human dignity.